Increased prevalence of parvovirus B19 infection among pregnant women in central Italy and genomic analysisAJOG Global Reports at a Glance - Alessandra Amendola, PhD; Cesare Ernesto Maria Gruber, PhD; Giuseppina Liuzzi, MD; Martina Rueca; Sara Belladonna; Antonella Giancotti, MD; Enrico Girardi, MD; Fabrizio Maggi, MD (AJOG Global Reports, 2025)
BACKGROUND: During 2024, the number of pregnant women who tested positive for parvovirus B19 in central Italy significantly increased. Genome sequence analysis of parvovirus B19 detected in blood samples of pregnant women revealed the co-circulation of 2 distinct clusters belonging to genotype 1, with nucleotide differences in both nonstructural and VP1 and VP2 proteins. The European Centre for Disease Prevention and Control declares a considerable increase in parvovirus B19 infections among children, pregnant women, and blood donors across most European nations from late 2023. OBJECTIVE: This study aimed to evaluate the positivity rate of parvovirus B19 infections among Italian pregnant women attending the maternal-fetal infection prevention outpatient care facility at the National Institute for Infectious Diseases Lazzaro Spallanzani of Rome for routine evaluation of maternal-fetal infections. STUDY DESIGN: Blood samples from 139 pregnant women were analyzed for parvovirus B19 infection according to the physician’s request: parvovirus B19 immunoglobulin M and immunoglobulin G antibodies and/or parvovirus B19 DNA. Among these samples, 8 positive for parvovirus B19 DNA were subjected to target amplicon sequencing and whole-genome reconstruction. For phylogenetic analysis, all parvovirus B19 complete genome sequences were collected, and multisequence alignment was performed to develop the best tree model. RESULTS: A sharp increase in parvovirus B19 circulation among Italian pregnant women occurred, starting from the end of 2023. During the first 9 months of 2024, requests for diagnosis of parvovirus B19 infection continued to increase significantly, and 46% of the samples analyzed in the first 9 months of the year were positive for parvovirus B19 infection. Phylogenetic analysis showed that all viruses detected belonged to parvovirus B19 genotype 1 and were clustered in 2 separate phylogenetic groups: one similar to the PP818758 genome sequence from France in 2024 and one similar to the KM393165 genome sequence from the United States in 2013. In addition, whole-genome sequence alignment revealed nucleotide mutations that caused amino acid changes, distinguishing the National Institute for Infectious Diseases clusters from similar sequences: the F8L, R54K, and F517S substitutions in the nonstructural gene of the viral genome for cluster 1 and the C298S, E195D, and T456S mutations in the nonstructural, VP1, and VP1 + VP2 genes for cluster 2. Furthermore, the C298S mutation was observed for the first time, as this mutation has never been detected in any other parvovirus B19 genome sequences submitted to international databases. CONCLUSION: Since the beginning of 2024, Italy, similar to many European countries, has been experiencing an epidemic of parvovirus B19 infection among pregnant women, with a positivity rate increasing to 46% in the first 9 months of the year. The peak incidence observed in this period seems to be significantly higher than that observed in the same period of the years 2021–2023. Because parvovirus B19 infection can cause up to 20% of asymptomatic infections with serious consequences for the fetus, it is essential to enhance screening and surveillance to stop virus transmission and dissemination, particularly during epidemic periods.